First one:

y= 2x - 1

Try rearranging this equation to get x by itself.

You should get x = (y + 1) / 2

Now, from here, plug this value of x into your other equation. This should get rid of any x's in your equation, making it possible to solve.

y = 1/x

Turns into

y = 1/[(y + 1)/2]

You're dividing by another fraction so multply it by it's reciprocal.

y = (1 * 2) / [(y + 1) * 1]

y = 2/(y + 1)

y(y+1) = 2

y² + y - 2 = 0

(y - 1)(y + 2)

The answer is 1 and -2.

-----

From here, you should be able to do the other two. Just remember to always get x by itself.